Does the law have the right to be powerless? Opinions of the employees of MOPS Zielona Góra regarding the causes of alcohol-related damage in fetus and prevention (of FASD) (Discourse of Law and Administration, 2021)
The consumption of alcoholic beverages by pregnant women is the cause of alcohol-related damage to the fetus, a serious and incurable disease. At least 9000 children were victims of this in Poland. This is a dramatic medical, ethical, social, economic and legal problem. Polish law has no effective tools to counter the causes of FASD. Our work shows these problems in the light of the opinions of employees of the municipal social assistance center (MOPS) in Zielona Góra, in other words, people who very often encounter alcohol consumption by pregnant women and the dramatic fate of their often seriously ill children. Their observations are critical. They point out the lack of effective tools to counter the causes of FASD and to help the affected children.
Keywords: FASD; opinions of social workers; causes; effects; MOPS Zielona Góra